SOCIAL AND EMOTIONAL LEARNING AS A FACTOR OF SELECTION OF NON-VIOLENT BEHAVIOR STRATEGIES AMONG STUDENTS - Mykhailo М. Alokhin (Вісник Університету імені Альфреда Нобеля. Серія Педагогіка і психология)
The article is devoted to the consideration of various social and emotional training programs that were developed and implemented in suchcountries as Norway, USA, Australia with the purpose of improv- countries as Norway, USA, Australia with the purpose of improv countries as Norway, USA, Australia with the purpose of improving discipline and overcoming the negative, antisocial behavior of high school students and the formation of their proactive attitudes. The UNICEF`s statistic research on the scale of bullying in Ukraine is presented. A review of educational innovations of inside schools in the issue of prevention of violent behavioral strategies was made, which underlines the importance of the chosen vector of achieving zero discrimination in educational institutions through the implementation of social-emotional programs in education. The article describes in detail the conceptual basics, parameters of implementation and the effectiveness of such programs: countering bullying Olveyus, “Friendly Schools” Australia, positive behavioral influence and support (PBIS), “Fast Track”, justice renewal (RJ), school psychiatric counseling, “PPCT,” and their inside analogue – the program for the development of personal and social competencies” Lions Quest”. After analyzing numerous studies on the effectiveness of these initiatives, we summarize that thanks to the introduction of individual elements of socio-emotional education, experimental schools have achieved important characteristics such as consistency of environment, as well as increasing students’ positive self-esteem, level of empathy, social skills, autonomous self-management skills, behavioral skills and conflict resolution. In addition, involvement in such programs contributes to the harmonization of the school climate, appropriate teachers’ attitudes.